PUSAT BUDIDAYA TANAMAN HIDROPONIK DI BANJARBARU - Raharja, Afif Apta; Hartono, Rudi (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The food demand in Banjarbaru City is directly proportional to the population growth. The conditions of Banjarbaru City make general farming activities difficult due to the limited availability of suitable land for cultivation, as well as the provision of facilities that function to make the flow of hydroponic plant production activities more directed and produce space effectively. This raises the issue of designing a hydroponic cultivation center that utilizes space effectively with limited land in urban areas. The method refers to the method of space programming that maps each building according to its respective function and is interrelated with each other. Thus, the concept that is raised is a functional hierarchy where hydroponic cultivation activities become the primary and supporting elements of cultivation activities become effective referring to the method of space programming that arranges each building according to its function effectively and orderly.